Queixas relacionadas à sexualidade no puerpério: uma revisão da literatura - Sousa, Iury Gabriela Terreço de (Universidade Federal do Tocantins, 2020)
In addition to all the adaptations with the arrival of the child, in the postpartum parents have another challenge, the adaptation of life to two. Objective: The study aimed to identify the main complaints reported by mothers related to the sexual pattern. Methodology: This is an integrative literature review, which searched scientific publications from 2010 to 2019, on the online platform GOOGLE ACADEMIC. Using the following keywords: "Puerperium", "Pregnancy", "Sexuality" and "Nursing". Used terms: "Puerperium and Sexuality", "Postpartum and Sexuality". Results: The results found were complaints such as fear of pain in sexual intercourse, dissatisfaction with self-image, change in routine, fear of getting pregnant again, presence of the baby in the bedroom, concern about partner satisfaction and discomfort with the presence of breast milk.Final considerations: The puerperal pregnancy process alters the woman's body perception and sexuality through mainly physical and hormonal changes, besides, of course, the change in family dynamics and routine. From this this resignification of a woman's sex life can be positive or negative.